2022
DOI: 10.3389/fped.2022.829420
|View full text |Cite
|
Sign up to set email alerts
|

Heart Involvement in Multisystem Inflammatory Syndrome, Associated With COVID-19 in Children: The Retrospective Multicenter Cohort Data

Abstract: ObjectivesHeart involvement in multisystem inflammatory syndrome associated with COVID-19 in children (MIS-C) is a new challenging problem, requiring fast and reliable diagnostics and appropriate treatment. The aim of this study is to describe heart involvement in patients with MIS-C.Study DesignIn this retrospective, multicenter cohort study, data of 122 patients were included. All patients met WHO and CDC criteria of MIS-C.ResultsVarious types of heart involvement in MIS-C patients were observed. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
2
6
0
2
Order By: Relevance
“…Involvement of the cardiovascular system took place in 50% of patients in our study. Similar figures appear in the articles of other researchers, where it is described with a frequency from 33 to 67% [ 35 , 36 , 37 ]. The main cardiovascular manifestations in MIS-C were shock, cardiac arrhythmias, myocardial and pericardial damage, and dilatation of the coronary arteries [ 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…Involvement of the cardiovascular system took place in 50% of patients in our study. Similar figures appear in the articles of other researchers, where it is described with a frequency from 33 to 67% [ 35 , 36 , 37 ]. The main cardiovascular manifestations in MIS-C were shock, cardiac arrhythmias, myocardial and pericardial damage, and dilatation of the coronary arteries [ 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…1 Over 9,400 cases and 79 deaths due to MIS-C have been reported in the US. Studies published to date reported clinical and laboratory findings that could be associated with cardiac involvement and disease severity in patients with MIS-C. [6][7][8][9] Our prospective observational study has similar findings in terms of increased risk of cardiac involvement with increased inflammatory markers. However, there was no difference in cardiac and treatment outcomes related to erythrocyte sedimentation rate.…”
Section: Discussionsupporting
confidence: 79%
“…According to the results of previous studies, AST, URE, and CK-MB were the biochemical indexes of liver dysfunction (Pilut et al, 2022 ), kidney injury (Zammel et al, 2022 ), and heart injury (Pilut et al, 2022 ), respectively. Elevated LDH levels were also often found in patients with myocarditis (Kostik et al, 2022 ). It cannot be ruled out that HBoV may affect these organs simultaneously, but it is equally possible that these observations are attributable to indirect immune responses of various organs to pathogens (Izumikawa, 2016 ).…”
Section: Discussionmentioning
confidence: 99%